Trends in prescribing colour contact lenses in private practices in Selangor, Malaysia from 2013 to 2014 / Nur Famiera Atiqah Md. Azmi - Md. Azmi, Nur Famiera Atiqah (2016)
Background: The aim of this study was to see the trends in prescribing colour contact lenses in private practices in Selangor, Malaysia from the year 2013 to 2014. This study include the replacement schedule type, compare between new –fit and refit wear, types of tints that was mostly chose by wearers, water content, average time colour contact lens likely to be worn and the modality of the colour contact lens. Methods: Questionnaires were sent out via mail (online survey monkey) to about 250 private practices around Selangor, Malaysia. Results: Over one year survey period, 53 online surveys were received. The age that wear lens was >21 years, adult (69.8%). 41.5% female wears colour contact lens compared to 3.8% male wearers. Continuous declined in colour contact lens prescribing, it can be seen from the findings of new-fit (5.7%) and refit (26.4%) over the one year of study. The type of tints that are chosen by the colour contact lens wearers were brown (92.45%) and gray tints (94.34%). Colour contact lens wearers were categories as full-time wearers due to colour contact lens wearers mostly wear contact lenses more than 5 days per week (49.1%). Replacement schedule types of colour contact lenses were monthly basis (77.4%). The type of water content that preferable was conventional 40 to 60% type of contact lenses (67.9%). Conclusion: This survey has revealed the trends in prescribing colour contact lens in private practices in Selangor, Malaysia over the one year of study from 2013 to 2014. The colour contact lens was higher in female wearer compared to male population. The wearers opted to choose monthly replacement for the replacement schedule type with the medium (40-60%) water content contact lens. The number of new fit for colour contact lens was quite low compared to refit. It was also found that, the wearers mostly worn the colour contact lens for 5 days per week.